Outcome of short segment posterior instrumentation with index level pedicle screw over thoracolumbar fracture - Muhamad Nurasnol bin Khamis
This is a longitudinal prospective study of 20 patients with Thoracolumbar fracture treated with short segment posterior instrumentation with index level pedicle screw in Hospital Sultanah Aminah, Johor Bahru, Johor. The aim of this study is to evaluate radiological and functional outcomes of patient after the short segment posterior instrumentation with index level pedicle screw at 6 months postoperative. 20 patients were selected and agreed to participate in this study. They were evaluated for the radiological outcome using Sagittal Index (SI) and Anterior Vertebra Height (AVH). Functional outcome was evaluated using Denis pain scale, Denis work scale and quality of life SF-36 questionnaire. 15 patients were male and 5 were female. The median patient age was 32.5 years (range, 18-58 years). 60% of patients work as a laborer and another 40% as a desk job. About 60% of injuries were due to the road traffic accident with the remaining 40% were due to fall from height. The majority of thoracolumbar monosegmental fractures were located at L1 and L2 with 7 cases each, followed by T12 and L4 with 2 cases each, 1 case for T11 and L3. Most of the fractures were AO types A3 in 13 cases, followed by A1 in three cases and two cases each in type A4 and B2. The mean operation time was 116±24 (minutes). The median postoperative hospitalization time was 4 days (range, 3-7 days). A median of 16.4° (range, 0-28) of kyphosis correction was attained from pre-operation to post-operation (p<0.001) with a maximum loss of correction at 6 months only 8° (p<0.05). A median elevation of AVH on postoperative radiograph was 37.6% (range, 2 to 56%) from pre-operation to post-operation (p<0.001) and maintained 33.1% at the time of review (p<0.001). At final follow-up none of the patients reported severe, intractable pain, 18 patients (90%) were able to work full time, and only 2 patients (10%) return to work as part-time. SF 36 quality of life showed 65% and 60% of patient had physical and mental health at least similar an average population. As a conclusion, addition of index level pedicle screw in short segment posterior instrumentation provide safe and effective treatment of the thoracolumbar fracture, prevent loss of reduction, maintain the stable construct, and saving more spinal motion segment. There were no correlation in between radiological and functional outcome.